ANALISIS HUKUM TERHADAP PENOLAKAN SUAMI MENGUCAPKAN IKRAR TALAK DALAM PERKARA PERCERAIAN - Soleh, Yudi Prihartanto (Faculty of Law, Universitas Pasundan, 2022)
A husband who does not want to divorce may apply to the Religious Courts with the intention to delay the divorce by not declaring the pledge of divorce even though the case is final and binding. If the wife who files for divorce and the case has been decided, automatically the husband and wife are divorced. In case the divorce is filed at the same time, either one cannot file any lawsuit. When the husband does not exercise his right to make a divorce pledge, the wife then can only file a